Synthesis and Antimicrobial Study of Some Methyl 4-O-palmitoyl-α-L-rhamnopyranoside Derivatives - Mohammed Mahbubul Matin (Orbital: The Electronic Journal of Chemistry, 2014)
4-O-Palmitoylation of methyl a-L-rhamnopyranoside (2) was carried out via blocking-deblocking technique. Methyl a-L-rhamnopyranoside (2) was first converted into 2,3-O-isopropylidene derivative (5) which on palmitoylation followed by deacetonation gave the desired 4-O-palmitoylrhamnopyranoside (7) in good yield. A number of 2,3-di-O-acyl derivatives of 7 were also prepared to get newer rhamnopyranosides (8-14) of biological importance. All the rhamnopyranosides (2, 5-14) were employed as test chemicals for in vitro antibacterial and antifungal functionality test against ten human pathogenic bacteria and four fungi, respectively. The study revealed that some of the tested rhamnopyranoside derivatives showed excellent antimicrobial functionalities as compared to the standard antibiotic.